2009
DOI: 10.1007/s11259-008-9197-9
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of the normal bovine digit

Abstract: The purpose of this study was defining the normal structures of the digits and hoof in Holstein dairy cattle using Magnetic Resonance Image (MRI). Transverse, Sagital and Dorsoplantar MRI images of three isolated cattle cadaver digits were obtained using Gyroscan T5-NT a magnet of 0.5 Tesla and T1 Weighted sequence. The MRI images were compared to corresponding frozen cross-sections and dissect specimens of the cadaver digits. Relevant anatomical structures were identified and labeled at each level. The MRI im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 15 publications
2
16
1
Order By: Relevance
“…The cartilage and synovial fluid revealed moderate signal intensities and appeared grey. A similar pattern of MRI signal intensities was reported in MR imaged equine (Dyson & Murray, ; Smith et al, ), bovine (Raji et al, ) and camel cadaveric feet (Hagag et al, ). On the other hand, in T2‐W images the adipose tissue, fatty marrow and trabecular bones revealed a decrease in their signal intensities and exhibited a greyish‐white colouration, whilst the cartilage and synovial fluid appeared with much enhanced signal intensities compared to those in T1‐W images and appeared white.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The cartilage and synovial fluid revealed moderate signal intensities and appeared grey. A similar pattern of MRI signal intensities was reported in MR imaged equine (Dyson & Murray, ; Smith et al, ), bovine (Raji et al, ) and camel cadaveric feet (Hagag et al, ). On the other hand, in T2‐W images the adipose tissue, fatty marrow and trabecular bones revealed a decrease in their signal intensities and exhibited a greyish‐white colouration, whilst the cartilage and synovial fluid appeared with much enhanced signal intensities compared to those in T1‐W images and appeared white.…”
Section: Discussionsupporting
confidence: 74%
“…Thanks to the availability of cost‐effective low‐field MRI facilities, several descriptive studies of foot MRI anatomy were reported during the past two decades in several species including the canine (Ober & Freeman, ), equine (Kleiter et al, ; Smith, Dyson, & Murray, ), bovine (Raji, Sardari, & Mirmahmoob, ) and camel (Hagag et al, ). However, those entailed the buffalo foot is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were in line with those of Kraft and Gavin () in equine, Hagag and Tawfiek () in bovine and Ibrahim et al (, ) in camel. In addition to that, these advantages of CT and MRI providing excellent views of the cross‐sectional imaging aid in diagnosis of the musculoskeletal disorders (Raji, Sardari, & Mohammadi, , ). CT images provide excellent visualization of the bony structures and can differentiate osseous changes before they are clinically or radiographically apparent (Young, Samii, Mattoon, Weibrode, & Bertone, ), and also can be used for assessment of soft tissue structures (Awaad, Abdel Maksoud, & Fathy, ; Seddek, Abedellaah, & Awaad, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Abdellatif et al () in the same animal reported that the hoof capsule and its corium are best evaluated on sagittal and transverse MR images where the hoof was depicted with low signal intensity and cannot be observed on black background, while the corium visualized with intermediate signal intensity. On contrary, the hoof corium of bovine appears black on MRI (Raji et al, ). This variable pattern of tissue intensity on both CT and MRI might be due to either technical factors; different acquisition settings, variable magnetic field of MRI and apparatus used or species‐specific anatomic features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation